2008
DOI: 10.1002/rcs.187
|View full text |Cite
|
Sign up to set email alerts
|

Adapter for contact force sensing of the da Vinci® robot

Abstract: The new configuration of force sensors and the new AFF joint work well in their basic functions. The total force-sensing error is estimated as approximately 0.5 N. One of the main reasons for the error appears to be the deformation of the adapter frame.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 40 publications
(16 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…This endoscopic robotic platform has entered the surgical realm for more than a decade in urologic, gynaecologic, cardiothoracic, and general surgery procedures (2)(3)(4)(5)(6). However, as it is not image guided and without a haptic interface, its application in spinal operations has been limited (7).…”
Section: Dear Editormentioning
confidence: 99%
See 1 more Smart Citation
“…This endoscopic robotic platform has entered the surgical realm for more than a decade in urologic, gynaecologic, cardiothoracic, and general surgery procedures (2)(3)(4)(5)(6). However, as it is not image guided and without a haptic interface, its application in spinal operations has been limited (7).…”
Section: Dear Editormentioning
confidence: 99%
“…More specifically, the investment cost for da Vinci W ranges from $1.1 to $1.7 million (5) and still lacks bone-cutting instruments and adequate force to perform basic curetting and rongeuring actions (9). Modified designs of guiding arms (14), along with implementation of haptic feedback (7) and integration of a stereotactic guidance system with the robot's software (5) would certainly add to its performance.…”
Section: Dear Editormentioning
confidence: 99%
“…Alternatively, the sensors can be attached to the proximal side of the tool, therefore placed outside the patient, however, this suffers from inaccuracies owing to friction and torques encountered at the incision point, as well as measured gravitational and inertial forces . A solution to deal with sensor corruption at the incision point is to isolate the sensors from the trocar using an overcoat, as done previously . In a force error estimate of 0.5 N was reported, in addition, multiple sensors were used and forces in the x and y direction were still measured at the tip of the instrument.…”
Section: Introductionmentioning
confidence: 99%
“…A solution to deal with sensor corruption at the incision point is to isolate the sensors from the trocar using an overcoat, as done previously . In a force error estimate of 0.5 N was reported, in addition, multiple sensors were used and forces in the x and y direction were still measured at the tip of the instrument. In , a modified trocar with integrated sensors was used, and the trocar was moved with the slave motion, and showed good results.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that RAMIS not only has the benefits of traditional minimally invasive surgery (MIS), such as reduced patient trauma and recovery time, lower morbidity and lower health care costs, but it also eliminates surgeon tremor, reduces the effects of surgeon fatigue and incorporates the ability to perform remote surgical procedures . However, previously proposed RAMIS systems, including the commercially available system called the da Vinci® Surgical System, suffer from lack of haptic feedback, which has negatively affected the surgeon's ability to palpate and diagnose tissue and differentiate its stiffness during surgery . Studies have revealed that force feedback helps the efficiency of teleoperation by reducing the peak magnitude of contact forces and trauma to the tissue, task completion time and number of errors .…”
Section: Introductionmentioning
confidence: 99%